Transcriptomic analysis delineates preterm prelabor rupture of membranes from preterm labor in preterm fetal membranes - Lori A. Underhill; J. M. Mennella; G. A. Tollefson; A. Uzun; B. E. Lechner (BMC, 2024)
Abstract Background Globally, preterm birth remains the leading cause of death in children younger than 5 years old. Spontaneous preterm birth is comprised of two events that may or may not occur simultaneously: preterm labor and preterm prelabor rupture of membranes (PPROM). To further explore the concept that spontaneous preterm birth can result from the initializing of two separate but overlapping pathological events, we compared fetal membrane tissue from preterm labor deliveries to fetal tissue from preterm labor with PPROM deliveries. We hypothesized that the fetal membrane tissue from preterm labor with PPROM cases will have an RNA-seq profile divergent from the fetal membrane tissue from preterm labor controls. Methods Chorioamnion, separated into amnion and chorion, was collected from eight gestationally age-matched cases and controls within 15 min of birth, and analyzed using RNA sequencing. Pathway enrichment analyses and functional annotations of differentially expressed genes were performed using KEGG and Gene Ontogeny Pathway enrichment analyses. Results A total of 1466 genes were differentially expressed in the amnion, and 484 genes were differentially expressed in the chorion (log2 fold change > 1, FDR < 0.05) in cases (preterm labor with PPROM), versus controls (preterm labor only). In the amnion, the most significantly enriched (FDR < 0.01) KEGG pathway among down-regulated genes was the extracellular matrix receptor interaction pathway. Seven of the most significantly enriched pathways were comprised of multiple genes from the COL family, including COL1A, COL3A1, COL4A4, and COL4A6. In the chorion, the most significantly enriched KEGG pathways in up-regulated genes were chemokine, NOD receptor, Toll-like receptor, and cytokine-cytokine receptor signaling pathways. Similarly, KEGG pathway enrichment analysis for up-regulated genes in the amnion included three inflammatory pathways: cytokine-cytokine interaction, TNF signaling and the CXCL family. Six genes were significantly up regulated in chorionic tissue discriminated between cases (preterm labor with PPROM) and controls (preterm labor only) including GBP5, CXCL9, ALPL, S100A8, CASP5 and MMP25. Conclusions In our study, transcriptome analysis of preterm fetal membranes revealed distinct differentially expressed genes for PPROM, separate from preterm labor. This study is the first to report transcriptome data that reflects the individual pathophysiology of amnion and chorion tissue from PPROM deliveries.